Impact Analysis of Income Tax Revenue on GDP Economic Growth of Nepal - Adhikari, Uttam (Interdisciplinary Journal of Management and Social Sciences, 2024)
This paper investigates the relationship between income tax revenue and GDP economic growth in Nepal from 2070 to 2079B.S. The study draws upon the Economic Survey of Nepal and the data produced by Nepal Rastra Bank. By employing a linear regression model, it reveals significant influence of income tax revenue on the progression of Nepal’s GDP. Methodology involves meticulous data collection and comprehensive statistical analysis. The linear regression model serves as the primary analytical tool to discern the nature and magnitude of the impact of income tax revenue on GDP economic growth. It demonstrates a positive relationship between income tax revenue and GDP progression, implying that an increase in income tax revenue correlates with a corresponding rise in Nepal’s economic growth. This outcome underscores the importance of effective tax policies and revenue collection mechanisms in fostering economic development and stability in the country. In conclusion, the empirical evidence presented here highlights the pivotal role of income tax revenue in shaping the country’s economic trajectory, making it an important area for policy intervention and reform as Nepal navigates its path towards prosperity in the 21st century.